After the Golden Age: The future of the welfare state in the new global order - Gøsta Esping-Andersen (United Nations Research Institute for Social Development (UNRISD), 1994)
The advanced welfare state, which became one of the hallmarks of the "Golden Age" of post-war prosperity, implied more than a mere upgrading of existing social policies in the developed industrial world. In the broadest of terms, it represented an effort to bring about economic, moral and political reconstruction. Economically, it departed from the orthodoxies of the pure market nexus and required the extension of income and employment security as a right of citizenship. Morally, it sought to defend the ideas of social justice, solidarity and universalism. Politically, the welfare state formed part of a project of nation building, affirming liberal democracy against the twin perils of fascism and bolshevism. Many countries became self-proclaimed welfare states, not so much to give a label to their social policies as to foster national social integration. In today's globally integrated open economies, however, many of the assumptions that guided post-war welfare state construction in the advanced industrial world seem no longer to obtain. Non-inflationary demand-led growth within one country now appears impossible; services rather than manufacturing must assure full employment; the population is rapidly aging; the conventional family, relying on the male breadwinner, is in decline; and the life course is both changing and diversifying. Such structural shifts challenge traditional social policy thinking.
Keywords: 330